Zu Briefbeförderung des Deutschen Ordens in Livland im 15. und 16. Jahrhundert. Die Eilbriefe - Kreem, Juhan (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2021)
On Delivery of Letters in the Teutonic Order in Livonia in the 15th and 16th centuries. Express Letters This contribution is on the organization and efficiency of the delivery of letters within the Teutonic Order in Livonia. Firstly, the scarce data on couriers and their duties is presented. The main part of the contribution discusses the phenomenon of registration of time (hour) and place in some of the stations on the delivery routes of letters. This method, also used extensively in Prussia, was most likely introduced in Livonia at the beginning of the fifteenth century. It was used in case of most urgent letters and was first and foremost meant to monitor the efficiency of delivery. The majority of the places of registration of time are in the territory of the Order, but there are also some exceptions, when this was done in episcopal castles or manors. A high number of letters of the Masters of the Teutonic Order in Tallinn City Archives also present the opportunity for some preliminary statistical analysis for understanding how space and time were mastered on the routes between Riga, Wenden, and Reval. It appears that, although the letters were ordered to be carried day and night, the calculated average speed was low, indicating some stops for rest along the road were also made.